Beda Pengaruh Antara Microwave Diathermy, Transverse Friction dan Mills Manipulasi dengan Microwave Diathermy dan Transverse Friction Terhadap Penurunan Nyeri Akibat Tennis Elbow Tipe II (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2007)
Objectives: The purpose of this study was to compare the intervention of MWD, trans-verse friction and mills manipulation with intervention of MWD and transverse friction towards consequence pain reduction tennis elbow type II. Methods: 16 person at me-disakti clinic - Sample at as into 2 groups that is 8 person in groups treatment at give therapy mwd, tranverse friction and mills manipulation and 8 person in control groups at give therapy mwd and tranverse friction. Tennis elbow be a disturbance that in group muscle ekstensor wrist especially in ekstensor carpi radialis brevis and longus. While tennis elboe type II be certain disturbance that in area teno periosteal ektensor car-piradialis brevis, where tenoperiosteal ekstensor carpi radialis brevis experience micro-ruptur pulling consequence that over do from muscle ekstensor carpi radialis brevis con-traction. Therapy gift mwd, tranverse friction and mills manipulation in condition tennis elbow type II can demote pain according to have a meaning and give influence differ-rence that have a meaning at compare therapy mwd and transverse friction. Result: This matter is proved in statistics testing that shows value p = 0,035, Intervention mwd, transverse friction and mills manipulation more have a meaning in demote consequence pain tennis elbow type II at compare with therapy mwd and transverse friction.keywords: Tennis Elbow, Manipulation, Intervention